Application of private international law in Islamic family law: a special reference to recognition of marriage in syariah court in Malaysia - Md Said , Muhamad Helmi; Abd Hak, Nora; Md Hashim, Noraini (2014)
In recent years, the phenomenon of globalization has provoked an increase of international disputes in family relationship. In Malaysia, due to growing international marriages, the Syariah Court in Malaysia cannot avoid and they have been forced to respond to this situation. Patterns and characteristics of International marriages have differed widely among world regions and races and therefore, needs theoretical explanation. It is not a matter of happily ever after, but most crucially to highlight the reality when problems arise. Due to the increasing number of International marriages and very limited research, this paper aims to discuss the application of Rules of Private International Law in Syariah Court in Malaysia. In this study, the data are obtained from materials consisting of textbooks, legal cases, Acts, journals, magazines, newsletters, newspapers, seminar and conference papers and unpublished writing (academic training, dissertation, and thesis involving investigation and analysis of the materials available in the library. Hence, it uses historical, analytical and comparative methods. This article is preamble to a more detailed study of the International marriages which the result will be useful for further improvement of the existing legal provisions in Malaysia.